2014
DOI: 10.1002/vnl.21420
|View full text |Cite
|
Sign up to set email alerts
|

Study on the physical and mechanical properties of electron‐beam‐irradiated Vinyl ester/TiO2 nanocomposites

Abstract: The effect of electron beam irradiation on the physical and mechanical properties of vinyl ester nanocomposites containing various amounts of TiO2 nanoparticles was investigated. The fracture toughness, surface hardness, and water uptake measurements were carried out to investigate alterations in the physical and mechanical properties owing to electron beam exposure. In this regard, it was attempted to infer the impact of TiO2 nanoparticles on the structural changes varying the irradiation dose. The results we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
4
3
0
Order By: Relevance
“…However, at the higher studied radiation dose (1000 kGy), the chain‐scissioning reactions in polymeric matrix dominated the cross‐linking reactions and the mechanical properties deteriorated. The same trend is reported by Shahrajabian et al …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…However, at the higher studied radiation dose (1000 kGy), the chain‐scissioning reactions in polymeric matrix dominated the cross‐linking reactions and the mechanical properties deteriorated. The same trend is reported by Shahrajabian et al …”
Section: Resultssupporting
confidence: 89%
“…However, at the higher studied radiation dose (1000 kGy), the chain-scissioning reactions in polymeric matrix dominated the cross-linking reactions and the mechanical properties deteriorated. The same trend is reported by Shahrajabian et al 16 The incorporation of carbon fiber intensely ameliorated the mechanical properties of the vinyl ester matrix (Figures 8 and 9). For example, the tensile strength of the pure vinyl ester polymer was increased from 13 to 435 MPa after reinforcement by carbon fiber.…”
Section: Mechanical Propertiessupporting
confidence: 88%
“…Also, in Figure 5 of SEM images, it was observed that with the presence of nanoparticles in the matrix, the degree of adhesion between resin and fibers has increased, which has increased the strength and hardness of the samples with 2 wt% silica nanoparticles. 79,11,12,26,27,31,3437
Figure 10.Force-extension diagrams for examples PF/CGF40% and PF/CGF50% (a) Tensile test (b) Bending test (c) Buckling test.
Figure 11.Force-extension curve of composite samples with different amplifiers (a) tensile test (b) bending test (c) buckling test.
…”
Section: Resultsmentioning
confidence: 99%
“…Also, in Figure 5 of SEM images, it was observed that with the presence of nanoparticles in the matrix, the degree of adhesion between resin and fibers has increased, which has increased the strength and hardness of the samples with 2 wt% silica nanoparticles. [7][8][9]11,12,26,27,31,[34][35][36][37] In the introduction section, the research conducted by Rostamian et al 19 for the fabrication of phenolic resin nanocomposites with short carbon fibers reinforced with silica and clay nanoparticles was given. that the nanocomposite samples were studied and examined in terms of strength and morphology properties by applying damage in a corrosive environment, and the results showed that with the increase in the weight percentage of short carbon fibers, the strength increases, but the plastic deformation is limited.…”
Section: Strength Propertiesmentioning
confidence: 99%
See 1 more Smart Citation